2004
DOI: 10.1159/000078007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of meiosis in azoospermic males: a joint histological and cytological approach

Abstract: We have developed a protocol for the identification of aberrant chromosome behavior during human male meiosis up to metaphase of the secondary spermatocyte. Histological evaluation by the Johnsen score of a testicular biopsy was combined with immunofluorescence of first meiotic prophase spermatocytes, using antibodies against synaptonemal complex protein 3 (SYCP3) and the product of the ataxia telangiectasia and rad3-related gene (ATR). This combination enables accurate meiotic prophase substaging and the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Later on, its further occurrence was confirmed in mice (de Boer and Branje 1979;Forejt and Gregorova 1977;Forejt 1979Forejt , 1996Forejt et al 1981), in humans (Johannisson et al 1983;Gabriel-Robez and Rumpler 1996;de Boer et al 2004;OliverBonet et al 2005;Sciurano et al 2007), and in other mammals (Power 1991;Jaafar et al 1992;Ansari et al 1993). These cytogenetic studies revealed the coincidence of chromosomal asynapsis, XY-autosomal colocalization, and male-limited sterility.…”
Section: Discussionmentioning
confidence: 91%
“…Later on, its further occurrence was confirmed in mice (de Boer and Branje 1979;Forejt and Gregorova 1977;Forejt 1979Forejt , 1996Forejt et al 1981), in humans (Johannisson et al 1983;Gabriel-Robez and Rumpler 1996;de Boer et al 2004;OliverBonet et al 2005;Sciurano et al 2007), and in other mammals (Power 1991;Jaafar et al 1992;Ansari et al 1993). These cytogenetic studies revealed the coincidence of chromosomal asynapsis, XY-autosomal colocalization, and male-limited sterility.…”
Section: Discussionmentioning
confidence: 91%
“…A first sign of H3.1/H3.2 loss was observed at mid pachytene when the XY axial elements locally start to unravel. (type III, [25], [41] (Figure 1A). In late pachytene XY bodies (types IV and V [25], [41]), when the XY axial elements appeared as a tangled knot of fibrils and DAPI was most intense, a highly variable H3.1/3.2 signal remained (Figure 1B, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the human XY body, features such as a condensed chromatin domain [23] and staining for γH2AX, BRCA1 [24] and ATR [25], were shown to be present as well. Also an indication for H3.1/3.2 nucleosome eviction was obtained [22].…”
Section: Introductionmentioning
confidence: 98%
“…When importing, data of the two observers were randomized if differences occurred, which was infrequent. Pachytene substages were determined, based on SYCP3 staining and electron microscopy surface spread images as described before by de Boer et al (Chandley et al, 1984;de Boer et al, 2004). The stages I, II and III were collectively labelled early and the stages IV and V as late pachytene spermatocytes.…”
Section: Image Capture and Analysismentioning
confidence: 99%
“…(i) In NOA patients, often a surplus of the early first meiotic prophase stages leptotene and zygotene is noted [(de Boer et al, 2004) and reviewed in (Martin, 2008)] indicating a problem with the homology search. (ii) in previous reports, an increased frequency of synaptic problems at pachytene was found in this category [reviewed in (Martin, 2008;Sun et al, 2007a)], as well as (iii) lower numbers of crossing-over (Gonsalves et al, 2004;Sun et al, 2007a) and (iv) increased levels of meiotic non-disjunction [reviewed by (Harton & Tempest, 2012;Martin, 2008)].…”
Section: Introductionmentioning
confidence: 99%